High Power Conversion Efficiency Narrow Divergence Angle Photonic Crystal Laser Diodes - Liang Wang; Aiyi Qi; Xuyan Zhou; Ting Fu; Chuanwang Xu; Renbo Han; Hongwei Qu; Wanhua Zheng (IEEE Photonics Journal, 2022)
9xx nm laser diodes (LDs) with aluminum component continuous gradient photonic band crystal (CCG-PBC) waveguide structure are designed and fabricated. The simulation results indicate that the CCG-PBC structure can significantly reduce the heterojunction barrier and carrier accumulation at the interface of the conventional PBC structure. We demonstrate that the LD with CCG-PBC structure can achieve a narrow vertical divergence angle of 16.2° at full width at half maximum, and the divergence angle changes with current not more than 0.5°. Meanwhile, the power conversion efficiency (PCE) of the narrow divergence angle LD can reach 66.7%, and the PCE at 20 W is still over 60%. After optimizing the coating reflectivity and cavity length of the CCG-PBC structure LD, the peak PCE and power are 71.5% and 17.2 W at 25 °C and 77.7% and 23.3 W at 0 °C, respectively, which are optimal results for any edge-emitting LD. Our device provides valuable guidance for researching high power and high efficiency narrow vertical divergence angle LDs.